2016
DOI: 10.1021/acs.biomac.6b00164
|View full text |Cite
|
Sign up to set email alerts
|

Size-Limited Penetration of Nanoparticles into Porcine Respiratory Mucus after Aerosol Deposition

Abstract: We investigated the rheological properties and the penetration of differently sized carboxylated nanoparticles in pig pulmonary mucus, on different distance and time scales. Nanoparticles were either mechanically mixed into the mucus samples or deposited as an aerosol, the latter resembling a more physiologically relevant delivery scenario. After mechanical dispersion, 500 nm particles were locally trapped; a fraction of carboxylated tracer particles of 100 or 200 nm in diameter could however freely diffuse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 27 publications
4
91
1
Order By: Relevance
“…Using MPT, Murgia et al, showed that 100 and 200 nm PS exhibited similar mobile fractions, 43 and 51% respectively, but based on FRAP analysis, the mobile fraction of 100 nm PS NP was twofold less than that of 200 nm PS NP. 98 These results suggest differences in short-versus long-time diffusion behavior of mucoadhesive PS NP in porcine airway mucus. Conversely, prior studies showed that nonmucoadhesive gene vectors that exhibited greater diffusion rates in human CF mucus, as assessed by MPT, also provided more widespread distribution in vivo throughout mouse airways following inhalation.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Using MPT, Murgia et al, showed that 100 and 200 nm PS exhibited similar mobile fractions, 43 and 51% respectively, but based on FRAP analysis, the mobile fraction of 100 nm PS NP was twofold less than that of 200 nm PS NP. 98 These results suggest differences in short-versus long-time diffusion behavior of mucoadhesive PS NP in porcine airway mucus. Conversely, prior studies showed that nonmucoadhesive gene vectors that exhibited greater diffusion rates in human CF mucus, as assessed by MPT, also provided more widespread distribution in vivo throughout mouse airways following inhalation.…”
mentioning
confidence: 87%
“…73 Similarly, 76% of 100 nm, 46% of 200 nm, and 86% of 500 nm PS NP were immobilized in ex vivo porcine airway mucus collected from excised tracheas. 98 FRAP is particularly useful in the assessment of the diffusion behavior of small NP with low fluorescence intensity and/or NP undergoing diffusion that is so rapid that reliable individual particle tracking (discussed in Section "Particle tracking") is not feasible. In addition, diffusion over physiologically-relevant distances (i.e., several microns) can be assessed using FRAP.…”
Section: Fluorescence Recovery After Photobleachingmentioning
confidence: 99%
See 3 more Smart Citations